Respuesta :

Vertex is (2,3), so that gives us:

    y=a(x-2)^2+3

Now the graph goes through (0,1), so plug that in to find a:

    1 = a(0-2)^2+3

  -2 = a(-2)^2

  -2 = a•4

 -1/2 = a

So, y = -1/2 (x-2)^2 + 3

   

Answer:

y = - ½(x - 2)² + 3

Step-by-step explanation:

Given the vetex, (2, 3), as the maximum point on the graph, along with the y-intercept, (0, 1):

We can substitute these values into the given vertex form of the quadratic equation:

y = a(x - h)² + k

where:

  • a = determines whether the graph opens up or down, and makes the parent function wider or narrower. If a is positive, the graph opens up; if a is negative, the graph opens down. If 0 < a < 1, the graph is wider than the parent function. If a > 1, the graph is narrower than the parent function.
  • (h, k ) = vertex
  • h = determines how far left or right the parent function is translated.
  • k = determines how far up or down the parent function is translated.

Use vertex = (2, 3) and y-intercept (0, 1) to solve for "a":

y = a(x - h)² + k

1 = a(0 - 2)² + 3

1 = a(-2)² + 3

1 = a(4) + 3

Subtract 3 from both sides:

1 - 3 = a(4) + 3 - 3

-2 = 4a

Divide both sides by 4 to solve for a:

-2/4 = 4a/4

- ½ = a

Therefore, the value of a = - ½. This means that the graph opens downward, and that the parabola is wider than the parent function.

The quadratic equation in vertex form given a = - ½, and vertex (2, 3) is:  

y = - ½(x - 2)² + 3

Please mark my answers as the Brainliest if you find this explanation helpful :)